Using Classroom Clickers to Increase Academic Engagement for Elementary School–Aged Students With Disabilities. Issue 2 (June 2022) - Watson, Tiffany; Berry, Brian
Student engagement is a critical feature to the teaching and learning dynamic that takes place in the classroom. Technology is often used as a means for increasing student engagement, and Student Response Technology (SRT), where students use handheld clickers to respond during classroom instruction, is one form of technology used to do this. The current study examined the effect of SRT on student engagement in elementary classrooms for students with disabilities. A multiple baseline across participants design was used to measure student engagement across several areas, including rate of participation and on-task behavior. Both visual and statistical analysis yielded a relationship between use of SRT and two areas of engagement: student's participation and on-task behavior.